Grado De Atención Al Usuario En Referencia Al Abastecimiento De Medicamentos En El Hospital General IESS – BABAHOYO - Pazmiño Triana, mayra Elizabeth (2018)
The Ecuadorian Institute of Social Security, based on the priority needs of the inhabitants of the Babahoyo canton, has had as main objective to provide medical attention to the affiliates of the aforementioned institution, with medical and paramedical personnel who perform their tasks jointly with the administration. of said Institution having as main mission the responsible and opportune attention to the Ecuadorian employee. This is located in the city of Babahoyo on Av. Juan Agnoleto and Av. 25 de Junio. The objective of the study is to establish and optimize the medication management process, so that the human, technical and administrative factors that are related to the process and allows to develop all activities efficiently. The